Application of MCDM-based TOPSIS method for the selection of optimal process parameter in turning of pure titanium. Issue 7 (2nd October 2017) - Khan, Akhtar; Maity, Kalipada
Abstract : Purpose: The purpose of this paper is to explore a multi-criteria decision-making (MCDM) methodology to determine an optimal combination of process parameters that is capable of generating favorable dimensional accuracy and product quality during turning of commercially pure titanium (CP-Ti) grade 2. Design/methodology/approach: The present paper recommends an optimal combination of cutting parameters with an aim to minimize the cutting force ( F c ), surface roughness ( R a ), machining temperature ( T m ) and to maximize the material removal rate (MRR) after turning of CP-Ti grade 2. This was achieved by the simultaneous optimization of the aforesaid output characteristics (i.e. F c, R a, T m, and MRR) using the MCDM-based TOPSIS method. Taguchi's L9 orthogonal array was used for conducting the experiments. The output responses (cutting force: F c, surface roughness: R a, machining temperature: T m and MRR) were integrated together and presented in terms of a single signal-to-noise ratio using the Taguchi method. Findings: The results of the proposed methodology depict that the higher MRR with desirable surface quality and the lower cutting force and machining temperature were observed at a combination of cutting variables as follows: cutting speed of 105 m/min, feed rate of 0.12 mm/rev and depth of cut of 0.5 mm. The analysis of variance test was conducted to evaluate the significance level of process parameters. It is evident from the aforesaid test that the depth of cut was the most significant process parameter followed by cutting speed. Originality/value: The selection of an optimal parametric combination during the machining operation is becoming more challenging as the decision maker has to consider a set of distinct quality characteristics simultaneously. This situation necessitates an efficient decision-making technique to be used during the machining operation. From the past literature, it is noticed that only a few works were reported on the multi-objective optimization of turning parameters using the TOPSIS method so far. Thus, the proposed methodology can help the decision maker and researchers to optimize the multi-objective turning problems effectively in combination with a desirable accuracy.